Incontinentia Pigmenti In A Male Infant: A Case Report - Kartika Dewi, Arifiana Wungu; Indraswari, Anindia; Citrashanty, Irmadita; Iskandar Zulkarnain; Sawitri; Yuri Widia (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Incontinentia pigmenti (IP), also known as Bloch-Sulzberger syndrome, is a rare X-linked dominant genodermatosis with an estimated incidence of 0.7–1.2 per 100,000 live births. It is caused by mutations in the IKBKG gene. Affected women have a 50% chance of transmitting the defective gene, while male fetuses usually do not survive due to the lethal effect of the mutation. Purpose: This report aims to present a rare surviving male case of incontinentia pigmenti with early dermatological manifestations and to highlight the importance of clinical recognition and multidisciplinary follow-up. Case: A 4-day-old male newborn presented with blisters on the left leg since birth. Dermatological examination showed multiple papules and vesicles arranged along Blaschko’s lines on erythematous macules without erosion. Based on clinical findings, the patient was diagnosed with stage 1 incontinentia pigmenti. Management included the use of moisturizers, topical antibiotics, and parental education regarding potential multi-organ involvement. Regular monitoring for neurological and ophthalmological manifestations was advised. Discussion: Incontinentia pigmenti is caused by an IKBKG gene mutation that disrupts NF-κB signaling, leading to increased apoptosis. It mainly affects ectodermal tissues such as the skin, hair, teeth, eyes, and CNS. The disease progresses through four skin stages: vesiculobullous, verrucous, hyperpigmented, and atrophic/alopecic. Diagnosis is mostly clinical, with histopathology or genetic testing used in atypical cases. Skin lesions usually resolve on their own, but preventing secondary infections is important. Conclusion: Incontinentia pigmenti in male infants is exceedingly rare. Early recognition, supportive care, and vigilant multidisciplinary monitoring are crucial to detect and manage possible systemic complications